Run for your life [a novel] - Patterson, James, 1947-; Ledwidge, Michael; Cannavale, Bobby; Roberts, Dallas (Westminster, Md. : Books on Tape, 2009)
A calculating killer who calls himself The Teacher is taking on New York City, slaughtering the powerful and the arrogant. Everyone is his potential student -- from the loudmouthed girl on her cell phone to the city's snooty upper crust. For some, it seems that the rich are finally getting what they deserve. For New York's elite, it is a call to terror. A secret pattern emerges in The Teacher's lessons, leaving Detective Michael Bennett just a few precious hours to save New York from the greatest disaster in its history.
Subtitle from book and container.
Unabridged.
Books on Tape: 7913-CD.
Narrators: Bobby Cannavale and Dallas Roberts.
Compact discs.
swfcd05/09.
Keywords: Rich people -- Fiction; Serial murderers -- Fiction; New York (N.Y.) -- Fiction; Suspense fiction